Design and evaluation of a quorum–based synchronisation protocol of multimedia replicas. (21st November 2014) - Duolikun, Dilawaer; Aikebaier, Ailixier; Enokido, Tomoya; Takizawa, Makoto
We discuss how to efficiently synchronise multiple replicas of a multimedia object. Multimedia replicas are characterised in terms of not only data structure but also quality of service (QoS). A replica is updated in enriching and impoverishing types of write operations where some data is added and removed in the replica, respectively. Computation resources are spent to materialise, i.e., physically update multimedia replicas. We discuss an extended multimedia quorum–based (EMQB) protocol to reduce the processing overhead of each replica. Here, a replica is not materialised in an impoverishing type of write operation. Even in an enriching type of write operation, only some number of replicas in a write quorum are materialised. Hence, every newest replica might not be materialisable in a read quorum. In the EMQB protocol, replicas are randomly selected to be in a read quorum until at least one newest, materialisable replica is found. The EMQB protocol is evaluated in terms of the total processing overhead of replicas compared with the quorum–based (QB) protocols. We show that the processing overhead of each replica can be reduced in the EMQB protocol.